NEW CROATIAN LAW ON ADMINISTRATIVE DISPUTES (EU and comparative law issues and challenges series (ECLIC), 2024)
After more than a decade of extensive reform of administrative litigation, which, despite clearly defined goals, did not yield the expected results, and after numerous requests and criticisms from practice and legal theory, a new Law on Administrative Disputes has been prepared. It contains numerous innovations primarily aimed at increasing the efficiency of administrative litigation. The paper presents and analyzes the basic novelties introduced by the new legislation.